A time-scaled convolution approach to construct IVIVC for enteric-coated acetylsalicylic acid tablets - Al-Gousous, J; Langguth, P (Pharmazie, 2018)
A scaled convolution-based in vitro-in vivo (IVIVC) model was constructed for two enteric-coated acetylsalicylic acid tablet formulations. The in vitro data used were the results of dissolution testing performed using three different dissolution methods: the United States Pharmacopoeia (USP) method, a method employing blank Fasted State Simulated Fluid (FaSSIF), and a new method developed in house. The in vivo data were obtained from a pharmacokinetic study on human subjects in the fasted state. When the new dissolution method results were used, an average prediction error less than 10% and a maximum prediction error less than 15% were obtained for the peak plasma concentration (Cmax) and area under the curve (AUC) parameters, thus meeting the internal validation criteria of the IVIVC guidance of the US Food and Drug Administration (FDA).